Impact of Oil Price, CO2 Emissons, Inflation and Economic Growth on FDI Inflow: Case of Kazakhstan - Kakizhanova, Tolkyn; Askarova, Zhanar; Amirova, Ainur; Baitanayeva, Bakhyt; Andabayeva, Gulmira (International Journal of Energy Economics and Policy, 2024)
The aim of this article is to observe impact of mentioned indicators on FDI inflow in Kazakhstan. For this purpose, we used ARDL approach, also conducted testing for the correctness of the chosen method. The results obtained in the model indicate that inflation does not affect the flow of FDI in the short and long term. In addition, CO2 emissions have positive impacts on FDI both in the short and long term. It is essential to note that extensive research has supported the hypothesis of the benefits of FDI for the environment, since FDI brings not only a flow of money but also knowledge and technology that allow the development of environmentally friendly production. Here, the flow of FDI increases proportionally with increasing CO2 emissions, so we faced the opposite. As is surprising, the changes in oil price have no effect on FDI inflow in both terms as inflation. And GDP per capita has negative impact on FDI in both short and long runs too. This enables us to assume that the Kazakh economy is not very dependent on FDI and many state programs for the development and growth of the economy can be not particularly associated with FDI.